Stakeholder engagement communication in CSR: Evaluation of the 2023 student entrepreneurship program at PT Taman Wisata Candi Borobudur, Prambanan and Ratu Boko - Nur Safitri, Susiana; Lestari, Puji (Universitas Ahmad Dahlan, 2025)
This study evaluates stakeholder engagement communication in PT Taman Wisata Candi Borobudur, Prambanan, and Ratu Boko’s 2023 Student Entrepreneur Social and Environmental Responsibility (TJSL) Program to enhance its effectiveness and sustainability. Employing a descriptive qualitative approach through interviews, observations, and document analysis, the findings indicate that communication was predominantly one-way, mediated through mentor teachers without direct channels or structured feedback for participants. Such practices diverge from the principles of two-way symmetrical communication, thereby limiting dialogue and active involvement. To address this gap, the study introduces the CIRCLE Communication Evaluation Model, which integrates six dimensions: message clarity, information access, responsiveness, feedback continuity, learning documentation, and engagement impact. Theoretically, this research contributes by extending CSR communication studies with a focus on documentation and feedback loops dimensions often overlooked in existing models such as CIPP and IAP2. Practically, the proposed model offers a replicable framework for strengthening stakeholder engagement and supporting the sustainability of education-based empowerment initiatives within the state-owned enterprise (BUMN) context.